2009
DOI: 10.1177/030089160909500633
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Catenin Mutations are not Observed in Chronic Myeloid Leukemia

Abstract: Beta-catenin amino-terminal mutations are not observed or very rare and therefore are not the underlying mechanism of activated Wnt signaling in CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Studies have demonstrated that deregulation of Wnt signaling pathway plays a role in the pathogenesis of CML. However, β-catenin amino-terminal mutations are not observed or are very rare and therefore are not the underlying mechanism of activated Wnt signaling in CML[54]. There must be other mechanisms for deregulating canonical Wnt signaling in CML.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that deregulation of Wnt signaling pathway plays a role in the pathogenesis of CML. However, β-catenin amino-terminal mutations are not observed or are very rare and therefore are not the underlying mechanism of activated Wnt signaling in CML[54]. There must be other mechanisms for deregulating canonical Wnt signaling in CML.…”
Section: Introductionmentioning
confidence: 99%
“…29 Nuclear accumulation of β-catenin is limited to HSCs, where it is the driving force of self-renewal. [8][9][10][11] Granulocyte-macrophage progenitors from CML blast crisis or therapy resistant disease also displays self-renewal capacity, a feature they normally do not posses. 16 Aberrant Wnt signaling and β-catenin nuclear accumulation in granulocyte-macrophage progenitors were shown to be responsible for this observation.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Although mutations of β-catenin, APC, and Axin-2 are frequently observed in a variety of epithelial cancers, they are infrequent in CML and in leukemia in general. 9 Epigenetic silencing of Wnt inhibitors and the stabilization and accumulation of β-catenin in cancers with or without mutational activation of Wnt/β-catenin signaling are another mechanisms that are observed in many cancers. [21][22][23][24][25] These proteins are able to inhibit and/or change the activity of Wnt proteins, thereby act as moderators of the signaling cascade and demonstrate a high frequency of aberrant promoter methylation in tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 They are not, however, seen in leukemia. 75 Analyses of conditional ␤-catenin knockout mice show that ␤-catenin is essential to maintain ISCs 76 and HFSCs. 77 The role of Wnt/␤-catenin signaling in regulating HSCs, however, remains controversial.…”
Section: Negative Feedbackmentioning
confidence: 99%